The impact of investor sentiment on sectoral returns and volatility: Evidence from the Johannesburg stock exchange - Hilary Tinotenda Muguto; Lorraine Muguto; Azra Bhayat; Hawaa Ncalane; Kara Jasmine Jack; Saadia Abdullah; Thabile Siphesihle Nkosi; Paul-Francois Muzindutsi (Cogent Economics & Finance, 2022)
This study investigated the impact of investor sentiment impact on sectoral returns and their volatility on the Johannesburg Stock Exchange using a proxy-based composite investor sentiment index and generalised autoregressive conditional heteroscedasticity models. Overall, findings showed a negative relationship between prevailing sentiment and subsequent returns and a positive relationship between investor sentiment and sector returns volatilities. Additionally, there was evidence of variability of sentiment effects on the sector returns and volatilities. Accordingly, firms that raise financing through the stock market, portfolio managers with investments thereon and policymakers seeking to ensure that markets operate efficiently need to consider the impact of market-wide investor sentiment on volatility and returns.
Keywords: G10; G15; G17; G40; G41; 330; GARCH; returns; sentiment; South Africa; volatility